Molecular modeling of low bandgap diblock co-oligomers with π-bridges for applications in photovoltaics - Alves, Gabriel G.B. [UNESP]; Oliveira, Eliezer F.; Batagin-Neto, Augusto [UNESP]; Lavarda, Francisco C. [UNESP] (Elsevier, 2018)
Recently, the diblock co-oligomers concept, a new design method to obtain conjugated organic compounds for varied applications in photovoltaics was proposed. These materials combines the interesting properties of extended systems and the versatility of small molecules, leading to low bandgap materials with improved properties, such as adjustable open circuit voltages and promising optical responses. Aiming to evaluate possible improved routes for the design of such materials, in this report we present a study on the effect of π-bridges incorporation on the properties of diblock co-oligomers. Six different π-bridges were inserted between polythiofene (Th) and polypyrrol (Py) oligomers with five units, following the structure [Th]5-[π-bridge]-[Py]5. The geometry optimization and optical absorption studies were carried out in the density functional theory (DFT) and time dependent-DFT (TD-DFT) frameworks, respectively, using the B3LYP correlation-exchange functional and 6-31G(d,p) basis set. The results point out that compounds with improved opto-electronic properties can be obtained by an appropriated choice of the π-bridges. The possible improvements are associated with the higher delocalization of the π-systems on the molecules, reduction of the effective optical/electronic bandgaps, high optical transition probability between the new highest occupied and lowest unoccupied molecular levels (HOMO–LUMO), optimized charge transport properties and reduced exciton dissociation energies.
Keywords: Electronic structure calculation; Oligomeric system; Photovoltaics; Polypyrrol; Polythiophene; π-bridge